Down-Regulated miR-130a/b Attenuates Rhabdomyosarcoma Proliferation via PPARG - Pan, Yi; Li, Junyang; Lou, Susu; Chen, Wanbiao; Lin, Yihang; Shen, Nan; Li, Youjin (Frontiers in Molecular Biosciences, 2022)
Background: Rhabdomyosarcoma (RMS) is one of the most common types of soft tissue sarcoma in children with a low 5-year survival rate. The survival outcome has no significant improvements in the last 30 years. A miRNA profiling of RMS might provide a new insight to discover new molecular targets for therapy. Methods: We comprehensively analyzed the miRNA and RNA sequencing data from patients and the TARGET database to find the potential miRNA-mRNA axes and validated them in patients' samples. After the miRNA antagomirs were used to silence the target miRNAs in the cell model, qRT-PCR, western blotting, and proliferation assay were performed to explore the interaction between miR-130a/b and PPARG their effects. Results: In RMS Patients, the expression of miR-130a/b has increased and its related PPARG gene has been suppressed. Bioinformatic analysis shows the miR-130a/b could target the PPARG gene and inhibits the proliferation of human RMS cell lines. In addition, the rosiglitazone maleate could be active the expression of PPARG in human RMS cell lines to suppress the proliferation. Conclusion: miR-130a/b can regulate the malignant process of RMS via targeting PPARG. Furthermore, the PPARG agonist, Rosiglitazone maleate, which could attenuate proliferation in RD cells, might benefit RMS patients.